Lower body mass index potentiates the association between late-night dinner and the prevalence of proteinuria - Muratsu, Jun; Akasaka, Hiroshi; Kamide, Kei; Morita, Makiko; Hayashi, Masato; Nariyama, Ayaka; Okamoto, Kota; Wada, Tatsuya; Sakaguchi, Katsuhiko; Zhang, Yan; Masuda, Daisaku; Shigematsu, Takashi; et al. (Frontiers in Endocrinology, 2025)
BackgroundThe presence of proteinuria or microalbuminuria is significantly associated with an increased risk of cardiovascular disease and all-cause mortality. Several studies reported the association between unhealthy eating patterns and proteinuria. While unhealthy eating patterns are a risk factor for obesity, they have also been reported to be a health risk in non-obese people without kidney disease. This cross-sectional study aimed to assess the association between late-night dinner and the prevalence of proteinuria in non-obese subjects with normal renal function.MethodsThe present study included 2,127 participants (1,028 males and 1,099 females) with an estimated glomerular filtration rate ≥ 60 mL/min/1.73 m2 and no history of kidney disease who underwent a health checkup at Rinku General Medical Center. To evaluate the impact of late-night dinner on prevalence of proteinuria (defined as dipstick proteinuria of ≥ ±), we applied logistic regression models adjusted for clinically relevant factors.ResultsLate-night dinner was reported in 297 males (28.9%) and 176 females (16.0%). Multivariable adjusted logistic regression models showed that late-night dinner was significantly associated with the prevalence of proteinuria in males. This association remained significant in lower body mass index (BMI) males (BMI< 24.9 kg/m2), even after adjusting for clinically relevant factors (adjusted odds ratios were 3.57 [1.34-9.48] and 3.15 [1.22-8.13], respectively). In contrast, this association was not evident in participants with a higher BMI ≥ 24.9 kg/m2.ConclusionThe effect of late-night dinner on proteinuria may vary depending on BMI, particularly in males.